How does teachers' professional agency in the classroom change in the professional transition from early career teachers to more experienced ones?. (3rd July 2022) - E, Liyuan; Toom, Auli; Sullanmaa, Jenni; Pietarinen, Janne; Soini, Tiina; Pyhältö, Kirsi
ABSTRACT: Professional agency is key for teachers' professional development, for constructing their professional identity, and for promoting student learning. This longitudinal study explored the development of teachers' (N = 201) sense of professional agency in the classroom in the professional transition from early career teachers to more experienced ones. We used latent profile analysis to examine the individual variation and change in teachers' sense of professional agency in the classroom in a five-year follow-up. The results showed three distinctive profiles: a high sense of professional agency (64%), a moderate sense of professional agency (32%), and a low sense of professional agency (4%) in the classroom. The changes detected in the three teachers' sense of professional agency profiles varied. The profiles were associated with teacher groups (i.e., primary teachers, subject teachers, and special education teachers), but not with stress, attrition intention or school size. The results imply that teachers' sense of professional agency in the classroom does not always increase in tandem with experience, and thus, different kinds of support are needed for cultivating teachers' sense of professional agency over time.